What drives more for macroeconomic instability-carbon inequality or income inequality? Panel evidence from emerging economies - Sahu, Anjan Kumar; Mahalik, Mantu Kumar (Environment, development and sustainability, 2025)
Macroeconomic instability poses a significant risk that casts a shadow over the economy, environment, and society. Climate change and environmental degradation are risks to society subject to macroeconomic instability. Nevertheless, few studies have investigated the connection between macroeconomic volatility and ecological degradation, but the impact of inequality in emissions and income on macroeconomic instability remains untouched, especially in emerging economies. This study utilizes a balanced panel data of 22 emerging economies from 1996 to 2019 to unveil the effect of carbon and income inequality on macroeconomic instability. As control variables, we incorporate government expenditure, bank credit, and governance into the macroeconomic instability function. The outcomes of the baseline PMG-ARDL model imply that both carbon inequality and income inequality instigate macroeconomic instability. However, income inequality impedes macroeconomic stability more than carbon inequality. In addition, the results demonstrate that government expenditure reduces macroeconomic instability, whereas bank credit intensifies it. The results of FGLS estimation are also robust to the baseline model. These findings encourage policymakers in emerging economies to use various fiscal instruments to improve economic and environmental resilience and reduce carbon emissions and income inequality.